ISOLASI DAN AKTIVITAS LARVACIDA MINYAK ATSIRI AKAR (Curcuma mangga, Val.) TERHADAP LARVA Aedes Aegypti DAN PROFIL GC-MS NYA - Lolita, . (PHARMACIANA, 2012)
Curcuma mangga.,Val has been recognized as a traditional drug since a long time ago. The active ingrediences of this plant especially the volatile oil contains monoterpenes and sesquiterpenes. This research was aimed to study about the larvacideâs activity of the volatile oil Curcuma mangga., Val rhizome and also to analyze its chemical compounds using the GC-MS. The volatile oil was isolated from Curcuma mangga, Val with steam and water distillation. The test method for larvicide was done by dissolving the substances into water and added by Tween 20 10%v/v to the the volatile oil. The concentration of the volatile oil of Curcuma mangga,Val rhizome were 100 ppm, 150 ppm, 200 ppm, 250 ppm, 300 ppm, and 350 ppm. The concentration of positive control âabateâ were 0,01 ppm; 0,025 ppm; 0,05 ppm; 0,1 ppm; 0,5 ppm while as the negative control was Tween 20 solution. The perception time of larvaeâs mortality was 24 hours. The chemical compound of Curcuma mangga., Val can be analysed by the GC-MS. Data of larvaeâs mortality were used to estimate the values of LC50 with the probit analyzis method. This study showed that the volatile oil of Curcuma mangga, Val. have clear-brass colour, bitter taste, typically aromatic like mango, rendement equal to (1,23 Â± 0,029)% v/b and refractive index 1,4881. The value of LC50 for the volatile oil of Curcuma mangga, Val. rhizome is (216,17 Â±12,51) ppm while abate equal to (0,072 Â± 0,024) ppm. This finding indicates that abate were more potent to larvae of Aedes aegypti. The GC-MS showes 30 peaks chromatogram and six peaks which indicates the possibility of alpha-pinene, camphene, beta-pinene, beta-myrcene, eukalyptole, ar-turmerone presence.